PENGARUH ONLINE STORE ATRIBUT DAN E-SERVICE QUALITY TERHADAP CORPORATE IMAGE DAN DAMPAKNYA TERHADAP BUSINESS PERFORMANCE PERUSAHAAN BUSANA MUSLIM - Hidayat, Taufiq; Derrriawan; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The purpose of this study was to determine the effect of online store attributes and e-service quality on corporate image and its impact on the business performance of Muslim fashion companies Zoya and Rabbani. Respondents in this study are zoya and rabbani online consumers as many as 138 people. Analysis Techniques in this study use Structural Equation Modelling - Partial Least Square analysis. The results showed that the Online Store Attribute had a positive effect on Corporate Image, meaning that the better the Online Store Attribute, the higher the value of Corporate Image, E-Service Quality has a positive effect on Corporate Image, meaning the better E-Service Quality, the higher the value of Corporate Image, Online Store Attribute has a positive effect on Business Performance, meaning that the better the Online Store Attribute, the higher the value of Business Performance, E-Service Quality has no significant effect on Business Performance. it can be concluded that the better E-Service quality cannot have a significant influence on high business performance, Corporate Image has a positive effect on Business Performance, meaning the better the Corporate Image, the higher the value of Business Performance.